The Legal Perspective on Strengthening the Practice of Bank Guarantees in Indonesia: Revisiting the Provisions Related to Payment - Ramlan Ginting (Bank Indonesia, 2022)
This Article provides the legal perspective of the transaction of bank guarantees in the banking practice in Indonesia. It examines the provisions related to payment for bank guarantees by comparing the provisions related to payment for the bank garansi and that of the standby letter of credit or demand guarantee. The work shows that the bank garansi is dependent guaranty, whereas the standby letter of credit or demand guarantee is independent guaranty. The payment for the bank garansi is based on the actual default, whereas the payment for the standby letter of credit or demand guarantee is based on the statement of default. The primary obligation to pay for the bank garansi is that of the issuing bank or guaranteed party, while the primary obligation to pay for the standby letter of credit or demand guarantee is that of the issuing bank. And, as to the international counter guarantee, the conflicting provisions arise when it is asking the bank garansi as the domestic bank guarantee. The banks, companies and government agencies involved in the transaction of bank guarantees are encouraged to understand the implication of these findings and further prepare the appropriate solution.